2021
DOI: 10.1002/bab.2091
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amylase and cellulase production by novel halotolerant Bacillus sp.PM06 isolated from sugarcane pressmud

Abstract: A novel Bacillus sp.PM06 isolated from sugarcane waste pressmud was tested for extracellular α-amylase and cellulase enzyme production. The effect of different substrates, nitrogen sources, pH, and temperature on growth and extracellular enzyme production was examined. Bacillus sp.PM06 was able to grow with starch and carboxymethyl cellulose (CMC) as a sole source of carbon and ammonium chloride was found to be the best nitrogen source. Maximum enzyme production was obtained at 48 H for both α-amylase and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Similar findings were observed in Bacillus sp. PM06 [65]. In another study, maximum production of cellulase was observed at pH 9 by Bacillus sp.…”
Section: Cellulase Production and Characterization Effect Of Ph On Ce...mentioning
confidence: 92%
See 2 more Smart Citations
“…Similar findings were observed in Bacillus sp. PM06 [65]. In another study, maximum production of cellulase was observed at pH 9 by Bacillus sp.…”
Section: Cellulase Production and Characterization Effect Of Ph On Ce...mentioning
confidence: 92%
“…A similar outcome was discovered in Bacillus sp. PM06 [65]. Maximum cellulase production was reached within 72 h for both Streptomyces sp.…”
Section: Effect Of the Incubation Periodmentioning
confidence: 96%
See 1 more Smart Citation
“…Although mutants have been described in the literature regarding SecYEG components [10,[14][15][16], we use a different approach based on protein-protein interactions for the SecA proteins of the SecYEG system, TasA and TapA [12]. Tey are involved in the formation of bioflms and secretion of AmyE and AprE, which represent, respectively, amylase [17] and proteases [18][19][20][21][22]. For this work, recombinant proteins were fused with targeted proteins.…”
Section: Introductionmentioning
confidence: 99%
“…When salt is used as a preservation agent, halotolerant bacteria may contaminate the drysalted and brine-salted food products. In previous studies, halotolerant bacteria were isolated from salted fish [10], fish sauce [11], cheese brine [12], fermented food [13], salt crystal [14], sugarcane press mud [15], grasshopper sub shrimp paste [16], cheese rinds [17], and fermented Solanum macrocarpon food [18].…”
Section: Introductionmentioning
confidence: 99%